Sentido y alcance del artículo IV del Acuerdo sobre Enseñanza y Asuntos culturales de 1979 - Ceballos, Enrique Herrera (Ius canonicum, 2016)
The purpose of this paper is to address an issue that has not yet been the subject of significant study: religious education in teacher training, in light of the 1979 Agreement on Education and Cultural Affairs. The wording of Article IV of the Agreement on Education and Cultural Affairs seems clear and the courts have endorsed a literal interpretation of the text. However, there are also interpretive criteria and resources that render this view less apparent: the authoritative interpretation made by government bodies; the relative weight of the subject in teacher training programs; and the academic practice of public universities in Spain. An overall assessment of the criteria discloses that implantation in practice may be poor because it fails to respect the object and ends of the Agreement as such.